Nursing interventions in pain management in neonates admitted to Neonatal Intensive Care Units: Integrative review (Research, Society and Development, 2025)
Hospitalized neonates in intensive care units are often subjected to painful and invasive procedures. Although pain is an essential parameter, its assessment still occurs in a subjective manner, which compromises the quality of care provided. Objective: To describe, through the literature, nursing care in the management of pain in newborns admitted to Neonatal Intensive Care Units. Methodology: This is an integrative review conducted in the Virtual Health Library, with articles published between 2020 and 2024, in Portuguese and available in full. Fourteen studies were included, selected according to established criteria and analyzed following PRISMA recommendations. Results: It was evidenced that neonates are exposed to several painful procedures, with pain identified through physiological and behavioral signs. The application of scales such as NIPS, PIPP, and NFCS, although recommended and validated, is still limited. Among the methods used by the nursing team, non-pharmacological strategies stood out: non-nutritive sucking, administration of 25% glucose, breastfeeding, Kangaroo Care, facilitated tucking, immersion bath, and ofuro therapy. These resources proved effective in reducing pain intensity, promoting comfort, favoring clinical stability of the newborn, and also contributing to the humanization of care. Conclusion: Non-pharmacological methods represent practical and essential alternatives for nursing practice in NICUs and should be systematically implemented based on protocols that strengthen comprehensive and evidence-based care.